The role of engagement in the efficacy of mindfulness training for adolescents - Moran, Megan, author; Shomaker, Lauren, advisor; Lucas-Thompson, Rachel, advisor; Aichele, Stephen, committee member; Cross, Jeni, committee member (Colorado State University. Libraries, 2025)
Research suggests mindfulness-based intervention (MBI) may be effective in preventing mental health challenges during adolescence. Yet, MBI effects on health and wellbeing outcomes in adolescents are generally small and inconsistent across studies (Fulambarkar et al., 2023). Theory and empirical evidence suggest that engagement (i.e., degree productive involvement with an activity) may be a key change process underlying the effect of MBI on target intervention processes (Ben-Eliyahu et al., 2018). This mixed methods dissertation study is the first to rigorously test engagement as a mechanism of MBI in adolescents. Using longitudinal structural equation modeling in n=73 adolescents who received an MBI, I found that a) overall increases in engagement were associated with overall improvements in adolescent-reported emotion regulation, mindfulness and self-compassion, and b) when adolescents reported higher engagement, relative to their own average, at any given measurement interval, they reported improvements in emotion regulation and self-compassion at the subsequent measurement interval. Additionally, I embedded an explanatory sequential mixed methods study into the overall single-arm MBI trial and used quantitative measures of engagement to purposively sample a subset of n=25 adolescents for post-program interviews. Reflexive thematic analysis of these interviews revealed key barriers and facilitators to engagement, as well as ways that engagement in MBI is distinct from prominent conceptualizations of engagement. Taken together, findings provide preliminary evidence that engagement is an important underlying process in adolescent MBI.
Keywords: engagement; mindfulness-based intervention; mindfulness training; adolescence